Psyllotoxus griseocinctus thomson, 1868 (Coleoptera: Cerambycidae): A potential pest of roses in brazil revealed by its lifecycle and niche modeling - Souza, Diego S.; Lampert, Silvana; Sepúlveda, Tatiana A.; Sanz-Veiga, Priscila A. [UNESP]; Savaris, Marcoandre (My University, 2021)
We present the first formal record of the twig-girdler Psyllotoxus griseocinctus Thomson, 1868 (Cerambycidae: Lamiinae: Onciderini) attacking the rose, Rosa sp. (Rosaceae) in Southern Brazil. We provide photographs of the damage P. griseocinctus causes to the plant, as well as morphological descriptions of the immature stages and molecular diagnostic tools to identify this species. Additionally, we provide a modelled map with the known and potential distribution of P. griseocinctus and new host records for three plant species: the common walnut tree, Juglans regia L. (Juglandaceae); the cambucá tree, Plinia edulis (Vell.) Sobral (Myrtaceae); and the cherry tree, Prunus cf. serrulata Lindl. (Rosaceae).
Keywords: Crops; Host plants; Lamiinae; Longhorned beetles; Onciderini; Twig-girdlers